Interpretation of the past, present, and future of organoid technology: an updated bibliometric analysis from 2009 to 2024 - Qu, Baozhen; Mu, Qiang; Bi, Huanhuan; Chen, Yuxian; Wang, Qitang; Ma, Xuezhen; Lu, Linlin (Frontiers in Cell and Developmental Biology, 2024)
Organoid technology has been developed rapidly in the past decade, which involves the exploration of the mechanism of development, regeneration and various diseases, and intersects among multiple disciplines. Thousands of literature on 3Dculture or organoids have been published in the research areas of cell biology tissue engineering, nanoscience, oncology and so on, resulting in it being challenging for researchers to timely summarize these studies. Bibliometric statistics is a helpful way to help researchers clarify the above issues efficiently and manage the whole landscape systematically. In this study, we performed a retrieval and bibliometric statistical analysis for original articles that were included in the Web of Science database from January 2009 to May 2024. Keyword co-occurrence chart, literature co-citation and clustering chart were conducted to classify the status quo of the organoids and predict future research areas. Next, we had an in-depth interpretation of the development process of the field of organoid research, including the background and reasons for the emergence of technology, the organoid research from bench to bedsides, the progress of the most widely studied types of organoids, the application of materials and technologies in organoids, and the emerging organoid-immune co-cultures trends. Furthermore, we also discussed the pitfalls, challenges and prospects of organoid technology. In summary, this study provides readers straightforward and convenient access to the organoid research field.